Carbon-coated hollow mesoporous FeP microcubes: an efficient and stable electrocatalyst for hydrogen evolution - Zhu, Xiaohua; Liu, Mengjia; Liu, Yang; Chen, Ruwen; Nie, Zhou; Li, Jinghong; Yao, Shouzhuo (Journal of materials chemistry. A, Materials for energy and sustainability, 2016)
Carbon coated hollow mesoporous FeP microcubes derived from Prussian blue were superior in catalytic activity and durability toward electrochemical hydrogen evolution with an overpotential of 115 mV to drive 10 mA cm −2 . Carbon coated hollow mesoporous FeP microcubes derived from Prussian blue were superior in catalytic activity and durability toward electrochemical hydrogen evolution with an overpotential of 115 mV to drive 10 mA cm −2 .